REBRANDING PT DATA SARANA WISATA TRAVEL SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - KP, Alexander Dimas; Fianto, Achmad Yanu Alif; Budiharjo, Hardman (Jurnal Art Nouveau, 2015)
Abstract: PT Data Sarana Wisata Travel is is a tourism service provider company in Indonesia which is based in Surabaya. As a company that has been running for 3 years, the profit is relatively stagnant and need to be efforts to build a strong image to remain competitive in the Indonesian market. During this, PT Data Sarana have not do promotion agresively and media campaign that used by this company does not have concept design. The low awareness of the importance the media campaign, create a high probability of customers moving to another travel. Media campaigns are very important to build brand. Therefore, it is necessary to increase awareness of customer by doing branding and maintenance customers through the media campaign to maintain the position of PT Data Sarana Wisata from the competitors. In this rebranding takes several steps to obtain appropriate results, which begins with interviews and observations, collecting data from observation, briefing comes from the company, and then carried out the design process. Of the process, discovered a keyword that will be used for the reference design a media campaign, which is A Truly Enjoyable Experience.. This concept will be implement using some of trip photo of PT Data Sarana Wisata. The concept was subsequently applied in corporate identity and promotional media that can be able to increase customer awareness.Â Keywords: Design, Rebranding, Brand Awareness, A Truly Enjoyable, Â Experience.